Red territory: forging infrastructural power. Issue 1 (2nd January 2023) - Munn, Luke
ABSTRACT: Territorial power is enacted and contested through technical infrastructures. From financing submarine cables to constructing hyperscale data facilities and claiming 5G patents, Chinese technology firms such as Huawei have steadily assembled layers of informational architecture. The paper investigates these layers through the lens of the Tseung Kwan O Industrial Estate in Hong Kong. By tracing its construction, charting its connections and mapping its operations, the paper reveals how specific formations of technical power emerge. Such power is at once political in its shaping of subjects' lives and geopolitical in its support of sovereign visions. These 'technical territories' take strange forms, inhabiting particular jurisdictions while also extending far beyond them. Their technical conditions exert influence at scale, challenging conventional understandings of territory and suggesting a new site of contemporary power.